Dimensions Supporting and Inhibiting Pregnant Women in Using “Sayang Bunda” Application - Rahayu, Tiwuk Puji; Agushybana, Farid; Widjanarko, Bagoes (South East Asia Nursing Research, 2019)
The Maternal and Neonatal Health Surveillance Officer and the Public Health Center of Purwoyoso build the android application. This application aims to help pregnant women recognize their pregnancy health thereby can improve the pregnant women’s four-visit antenatal care coverage. This case study described the dimensions supporting and inhibiting pregnant women in the Puskesmas Purwoyoso work area conducted on August-November 2019. The informants of the research consisted of 42 pregnant women. Data collection was conducted using interviews and observation techniques. The instrument used was an interview guide, recorder, and observation sheet. The result of the research showed the factors supporting healthcare service in Semarang area, Semarang Health Office always monitoring the condition of pregnant women through the result of examination on pregnant women facilitation in the application, updating pregnancy article, making innovation of application to facilitate pregnant women in accessing and using the application. Puskesmas Purwoyoso promotes the application when pregnant women have their pregnancy examined in Puskesmas and the implementation of pregnant women class. The Maternal and Neonatal Health Surveillance Officer promotes the application when visiting the pregnant women’s house for facilitating the pregnant women. This application has an advantage over other pregnancy application so that pregnant women Puskesmas Purwoyoso work area can get many benefits. Inhibiting factor includes the highland condition of residence, pregnant women having no android smartphone and memory data of smartphone android of pregnant women has been full.